Temporal arteritis with erythrocyte sedimentation rate <50 mm/h: a clinical reminder - Cheema MR (Dove Medical Press, 2016)
Muhammad Raza Cheema, Shakawan M IsmaeelGeriatrics Department, Wirral University Teaching Hospital, Merseyside, United KingdomAbstract: Temporal arteritis, also known as giant cell arteritis (GCA), is a systemic vasculitis that predominantly involves the temporal arteries. It is a medical emergency and should be treated promptly as it can lead to permanent loss of vision. It is very commonly associated with a raised erythrocyte sedimentation rate (ESR), usually >50 mm/h, one of the essential criteria defined by the American College of Rheumatology classification of GCA. Here, we describe the case of a 73-year-old male presenting with a 2-day history of a sudden onset of a severe left-sided headache, which had the signs and symptoms consistent with GCA but he had an ESR of only 27 mm/h. The patient was urgently treated with prednisolone 60 mg per day, and his symptoms dramatically improved within 24 hours of therapy. Temporal artery biopsy results were consistent with an inflammatory response, and withdrawal of treatment led to a relapse of the symptoms. The patient was slowly tapered off the high steroid dose and is now currently managed on a low steroid dose. We should keep a high index of suspicion for GCA in patients presenting with clinical symptoms of GCA even though the ESR is <50 mm/h as stated in the criteria for GCA diagnosis.Keywords: temporal arteritis, giant cell arteritis, prednisolone, erythrocyte sedimentation rate